The Role of Online Resources in Developing Autonomous Learning Metacognitive Skills Among First-Year University Students of English: A Mixed Methods Study - Yahya Bouhafa; Shelby R. Hochberg (Institut Agama Islam Negeri Palopo, 2022)
This mixed methods study examines the way online resources can be effective in developing the learning autonomy metacognitive skills of planning, monitoring, and self-evaluation among undergraduate students at the Facultyof Letters and Humanities Fes-Agdal, which is representative of the socio-cultural and higher education system of Morocco. The sample consisted of an experimental group and a control group. The experimental group consisted of 120 students who were exposed to three main online tools (Newsela.com, mrnussbaum.com, and rewordify.com), with virtual meetings and instruction provided through Facebook. The Facebook groups were kept secret, with only participants joining. The control group consisted of 120 students that benefited only from the university’s regular reading courses. The experimental intervention period was followed by interviews with a sample of 25 students from both groups, providing a qualitative perspective. The overall results suggest that online resources have a positive effect on the development of metacognitive skills. Students tend to appreciate the inclusion of online resources in the classroom without devaluing the role of their EFL teacher – the students did not expect online resources to fully replace the role of their teachers.Keywords: EFL online learning autonomy; learning autonomy; online resources; teaching and learning in higher education